2018
DOI: 10.1172/jci.insight.122211
|View full text |Cite
|
Sign up to set email alerts
|

CCR10+ epithelial cells from idiopathic pulmonary fibrosis lungs drive remodeling

Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating fibrotic lung disease of unknown etiology and limited therapeutic options. In this report, we characterize what we believe is a novel CCR10+ epithelial cell population in IPF lungs. There was a significant increase in the percentage of CCR10+ epithelial cells in IPF relative to normal lung explants and their numbers significantly correlated to lung remodeling in humanized NSG mice. Cultured CCR10-enriched IPF epithelial cells promoted IPF lung fibroblast inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…The scRNA-seq data for lung airway epithelial cells (LAECs) was downloaded from the GEO database using accession number GSE115982. The original data was generated in the study of [32] for CCR10 − and CCR10 + LAECs. We used the data generated from the CCR10 − cells with the sample identifier GSM3204305.…”
Section: Non-lcl Scrna-seq Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scRNA-seq data for lung airway epithelial cells (LAECs) was downloaded from the GEO database using accession number GSE115982. The original data was generated in the study of [32] for CCR10 − and CCR10 + LAECs. We used the data generated from the CCR10 − cells with the sample identifier GSM3204305.…”
Section: Non-lcl Scrna-seq Data Setsmentioning
confidence: 99%
“…This data has been deposited in the NCBI Gene Expression Omnibus (GEO) database (accession number GSE126321). For the other two cell types, LAEC and DF, we obtained the scRNA-seq data for 3863 and 2553 cells from the studies of [32] and [33], respectively. In addition, we also processed two more samples for fibroblasts and one for iPSC cells (see Section 2.7. for data availability) to cross-validate our findings.…”
mentioning
confidence: 99%
“…First, EPHA3 is expressed predominantly in lymphocytes and encodes a receptor tyrosine kinase implicated in regulating cell adhesion and cellular motility [48]. A recent study demonstrated that a novel epithelial cell population derived from IPF lungs co-expressed EPHA3 and CC chemokine receptor (CCR)-10 and facilitated the development of lung remodeling [49]. CCL28, a chemokine ligand for CCR10, was upregulated in BALF in accordance with increased p38 activity ( Supplementary Table S1) [50].…”
Section: Discussionmentioning
confidence: 99%
“…This data has been deposited in the NCBI GEO database (Accession number GSE126321, Data Availability). For the other two cell types, LAEC and DF, we obtained the scRNA-seq data for 3,863 and 2,553 cells from the studies of (Habiel et al 2018) and (Hagai et al 2018), respectively (Materials and Methods). All scRNA-seq data sets of the three cell types were produced using 10X Genomics droplet-based solution and made use of unique molecular identifiers (UMIs) (Kivioja et al 2011).…”
Section: Single-cell Rna Sequencing and Selection Of Highly Homogenoumentioning
confidence: 99%
“…The scRNA-seq data for lung airway epithelial cells (LAECs) was downloaded from the GEO database using accession number GSE115982. The original data was generated in the study of (Habiel et al 2018) for CCR10 -and CCR10 + LAECs. We used the data generated from the CCR10 -cells with the sample identifier GSM3204305.…”
Section: Non-lcl Scrna-seq Data Setsmentioning
confidence: 99%